Monitoring Kinerja PLTS 2x100Wp Menggunakan Parameter Arus, Daya, dan Intensitas Matahari dengan Metode Eksperimen - Putri Amelia; Yudi Wijanarko; Sabilal Rasyad (Pusat riset dan Inovasi Nasional, 2025)
This research aims to monitor the performance of a 2x100Wp Solar Power Plant (PLTS) using the parameters of current, power, and solar intensity. The monitoring system is designed to record and analyze the electrical output of the solar panel in real-time. The experimental method is used by collecting data directly through current and voltage sensors, as well as light sensors connected to a microcontroller. Data was collected to see the relationship between solar intensity and electrical power generated. The test results show that the intensity of the sun greatly affects the amount of current and power generated by the solar panel. This monitoring system can be a tool for learning and analyzing the performance of small-scale solar power systems in a laboratory environment.